Misi Gereja : Tantangan Gereja Dalam Membawa Misi Allah Di Jemaat GMIBM Abraham Kotobangon Wilayah Kotamobagu - Arina, Hein; Tangkere, Merlisa (Educatio Christi, 2022)
The challenge of the church in carrying out God's mission is something that happens in reality, the church as a tool used by God to carry out His mission for His people, but in the midst of the church's efforts to carry out God's mission there are various challenges that o ften occur in carrying out God's mission. church, God's mission is not only limited to evangelism but all forms of church ministry are part of carrying out God's mission. In the midst of church life, the church in which there is an assembly, the congregation and even the entire ministry are called to be tools to carry out God's mission, they must understand correctly how the challenges occur and have a deeper knowledge of God's mission and mission. This journal has a goal in which people who believe in Him truly understand how God's mission is for mankind and what are the challenges of the church in carrying out the church's mission to realize God's mission for believers.